APPROACHES TO RELIGIOUS POETRY IN POLISH AND ANGLOPHONE SCHOLARSHIP. A COMPARATIVE OVERVIEW - Matyjaszczyk, Joanna (Prace Polonistyczne, 2020)
The article compares Polish and Anglophone literary-theoretical approaches to religious poetry. It demonstrates that some common tendencies to be found in Polish studies and in English scholarship include drawing on a single religious tradition (Christian, official), focusing on the author and their religious experience, and narrow and/or prescriptive approaches that are sometimes more theological than literary-theoretical in nature. The survey suggests that the most prominent difference is that Polish criticism has produced a long-standing tradition of literary-theoretical studies that develop on or polemicize with each other in an attempt to describe and systematize the field of the intersections of poetry and religion and propose literary methodologies for studying religious poetry, while Anglophone studies do not enter into this kind of dialogue. The Polish studies, if popularized, could help reduce the theoretical and methodological deficit in Anglophone scholarship on the subject.